The role of agrobusiness in the development of society and its opportunities - D. Dzhurayeva; Rakhmonov , Rustam (GREEN ECONOMY AND DEVELOPMENT, 2025)
The article examines the main opportunities for the development of agrobusiness, including the introduction of innovative technologies, the production of biotechnology and environmentally friendly products, access to new export markets, and the development of agrotourism in rural areas. It also emphasizes the importance of public-private partnerships, attracting investment in agroculture, and educating farmers. The article also shows that an integrated approach to the development of agrobusiness, including addressing economic, environmental, and social issues, can significantly contribute to improving well-being in rural areas, sustaining the country's economic growth, and protecting the environment.